Application Effect of Potassium on Rice (Oryza sativa L.) Recovery After Drought Stress - Handoyo, Tri; Hakim, Mohammad Sulton; Dewanti, Parawita; Hartatik, Sri; Slameto, Slameto (Jurnal ILMU DASAR, 2020)
The critical phase of rice plants on water availability includes the vegetative phase when tillering stage, generative phase 1 at panicle initiation stage and generative phase 2 when booting stage. The lack of water in the vegetative phase and in the generative phase will disturb the growth of rice plants. However, if the water needs are fulfilled immediately, the plants will recover and able to grow normally. The ability of plants to do recovery can be improved through the application of potassium fertilizer. This research aimed to determine the optimum dosage of potassium fertilizer when drought occurs in several critical phases to improve the recovery capability of the rice plant. This experiment used a completely randomized design (CRD) with 2 factors where the first factor was the dosage of potassium fertilizer using KCl fertilizer which was 50 kg/ha, 75 kg/ha, 100 kg/ha and 125 kg/ha. The second factor was the difference in the phase of stress, namely the vegetative phase at the time of tillering, the generative phase 1 at panicle initiation and the generative phase 2 when booting. Each treatment combination was repeated 3 times. Observation variables included Rice grain weight per clump, Proline content, Root Dry Weight, Relative Water Content (RWC) leaves, and Height of plants. The results of the study proved that the best dosage of KCl fertilizer to improve rice recovery ability is 100 kg/ha. Rice plants gripped in the vegetative phase have better recovery capabilities than those gripped in the generative phase.Keywords: Recovery, rice, drought stress and potassium.